Age-related similarities and differences in first impressions of trustworthiness. Issue 5 (3rd July 2016) - Bailey, Phoebe E.; Szczap, Paulina; McLennan, Skye N.; Slessor, Gillian; Ruffman, Ted; Rendell, Peter G.
Abstract : Trust is a particularly under-studied aspect of social relationships in older age. In the current study, young ( n = 35) and older adults ( n = 35) completed a series of one-shot social economic trust games in which they invested real money with trustees. There were potential gains with each investment and also a risk of losing everything if the trustee was untrustworthy. The reputation and facial appearance of each trustee were manipulated to make them appear more or less trustworthy. Results revealed that young and older adults invest more money with trustees whose facial appearance and reputation indicate that they are trustworthy rather than untrustworthy. However, older adults were more likely than young to invest with trustees who had a reputation for being untrustworthy. We discuss whether age-related differences in responding to negative information may account for an age-related increase in trust, particularly when trusting someone with a reputation for being uncooperative.